2003
DOI: 10.1021/la034466h
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry and Nitric Oxide Interaction of Heme Proteins Adsorbed on Nanocrystalline Tin Oxide Electrodes

Abstract: Nanocrystalline, nanoporous metal oxide films are a novel substrate for protein immobilization. Such electrodes allow both electrochemical and spectroelectrochemical studies of the protein redox function and, moreover, provide an attractive approach for the development of both optical and electrochemical biosensors. Previous studies have largely focused on the use of nanocrystalline TiO2 electrodes. In this paper, we extend these studies to nanocrystalline SnO2 electrodes. Immobilization of two proteins, cytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
154
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(168 citation statements)
references
References 23 publications
14
154
0
Order By: Relevance
“…Thus, the electrochemical investigations have been mainly performed with adding of mediators and promoters or modified and immobilized electrodes, i.e. by the MET types (Kafi and Crossley, 2013;Yin et al, 2005;Revenga-Parra et al, 2005;Topoglidis et al, 2003;Kawahara and Ohno, 1998;Shan et al, 2007;Shi et al, 2007;Zhao et al, 2006;Feng et al, 2006;Zhang and Oyama, 2004;Jia et al, 2004;Sun and Hu, 2004;Gu et al, 2001). On the other hand, we have demonstrated a simplest DET between Hb molecules and bare indium-tin-oxide (ITO) electrodes and found that the protein structure of Hb molecules on the bare ITO electrode surface should be similar to its own native state the same as that in the solution phase (Ayato et al, 2008;Ayato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the electrochemical investigations have been mainly performed with adding of mediators and promoters or modified and immobilized electrodes, i.e. by the MET types (Kafi and Crossley, 2013;Yin et al, 2005;Revenga-Parra et al, 2005;Topoglidis et al, 2003;Kawahara and Ohno, 1998;Shan et al, 2007;Shi et al, 2007;Zhao et al, 2006;Feng et al, 2006;Zhang and Oyama, 2004;Jia et al, 2004;Sun and Hu, 2004;Gu et al, 2001). On the other hand, we have demonstrated a simplest DET between Hb molecules and bare indium-tin-oxide (ITO) electrodes and found that the protein structure of Hb molecules on the bare ITO electrode surface should be similar to its own native state the same as that in the solution phase (Ayato et al, 2008;Ayato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the unique properties of nanostructures/nanomaterials in the biosensing area, nanosensors offer some significant advantages owing to their small size and high surface area to volume ratios allowing larger signals, better catalysis and the more rapid movement of analytes through sensors. Recently, nanostructured materials such as zinc oxide (ZnO) [10][11][12][13][14], cerium oxide (CeO 2 ) [15], tin oxide (SnO 2 ) [16], titanium oxide (TiO 2 ) [17], iron oxide (FeO 2 ) [18] and zirconium oxide (ZrO 2 ) nanoparticles [19] have been used for fabrication of transducer surface because of their unique ability to promote faster electron transfer between electrode and active site of desired enzyme. Among these nanomaterials, ZnO nanostructures receive growing attention due to their unique properties including high specific surface area, high catalytic efficiency, strong adsorption ability, high isoelectric point (IEP 9.5), wide band gap (3.37 eV), biocompatibility and high electron communication features.…”
Section: Introductionmentioning
confidence: 99%
“…The linearity range was obtained as 4-5 mM with detection limit 7.6 and 7.4 μmol/L and biosensor was stable up to 9 months. Attempts have been made to applied sol-gel tin oxide matrix to heme proteins immobilization for rapid detection of H 2 O 2 (Jia et al, 2005a&b;Topoglidis et al, 2003). Solgel derived bioelectrodes showed better analytical performance in respect to other conventional method prepared bioelectrodes, such as faster response, wider detection range, lower detection limit, better affinity, higher enzyme loading, simpler operation and better storage stability for electrochemical detection of hydrogen peroxide due to the introduction of the collagen to form well-distributed porous three-dimensional structure.…”
Section: Hydrogen Peroxide Biosensorsmentioning
confidence: 99%